The Macroeconomic Effects of Higher Oil Prices - Isard, Peter (IMF Working Papers; Working Paper, 2001)
The paper uses MULTIMOD to analyze the macroeconomic effects of oil price shocks, distinguishing between temporary, more persistent, and permanent shocks. It provides perspectives on several findings in the literature and the key role of monetary policy in influencing macroeconomic outcomes. Specific attention is paid to the channels through which oil price increases can pass through into core inflation, a possible explanation of the asymmetric relationship between oil prices and economic activity, the role of monetary policy credibility, the implications of delayed policy responses, and the relative merits of leaning in different directions when the correct policy response is uncertain.